2007
DOI: 10.1523/jneurosci.4759-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Learning-Induced Enduring Changes in Functional Connectivity among Prefrontal Cortical Neurons

Abstract: Current thinking about how memories are stored in the brain has been profoundly influenced by Donald O. Hebb's cell assembly hypothesis, which posits that (1) learning produces a stable alteration in patterns of connectivity among repeatedly coactivated neurons, and (2) memory retrieval involves reactivation of those altered patterns of connectivity. However, learning-induced changes in connectivity that persist over long periods of time have not been clearly demonstrated. In the present study, two spatial nav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 58 publications
4
34
0
Order By: Relevance
“…In addition, activity dependent changes in synaptic weighting are believed to underlie experiential learning throughout the life span, promoting the dynamic reconfiguration of neural networks to meet changing sensorimotor and cognitive processing demands (40)(41)(42). Sleep, particularly deep slow wave sleep, has been posited to represent a mechanism by which changes in synaptic weighting accumulated in wakefulness are homeostatically normalized (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, activity dependent changes in synaptic weighting are believed to underlie experiential learning throughout the life span, promoting the dynamic reconfiguration of neural networks to meet changing sensorimotor and cognitive processing demands (40)(41)(42). Sleep, particularly deep slow wave sleep, has been posited to represent a mechanism by which changes in synaptic weighting accumulated in wakefulness are homeostatically normalized (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, damage to the PFC produces impairments in various working memory tasks in humans and non-human primates (Kolb 1990;Fuster 1997;Stuss and Alexander 2000). Additionally, recording and brain imaging studies found neural activity correlates of working memory, i.e., increased PFC activity during the delay period (Fuster and Alexander 1971;Kubota and Niki 1971;Funahashi et al 1989).In rodents, a delayed alternation task (DAT; employing T, radial-arm, and figure-eight mazes) has been widely used to further investigate the PFC-working memory hypothesis (Murphy et al 1996;Zahrt et al 1997;Baeg et al 2003Baeg et al , 2007Schoenbaum et al 2003;Birnbaum et al 2004;Clinton et al 2006). In this task, the animal is typically cued (via a discrete or spatial stimulus) to make a choice response to obtain a reward, but is prevented from responding until after some delay period (or working memory demand) has been imposed.…”
mentioning
confidence: 99%
“…In rodents, a delayed alternation task (DAT; employing T, radial-arm, and figure-eight mazes) has been widely used to further investigate the PFC-working memory hypothesis (Murphy et al 1996;Zahrt et al 1997;Baeg et al 2003Baeg et al , 2007Schoenbaum et al 2003;Birnbaum et al 2004;Clinton et al 2006). In this task, the animal is typically cued (via a discrete or spatial stimulus) to make a choice response to obtain a reward, but is prevented from responding until after some delay period (or working memory demand) has been imposed.…”
mentioning
confidence: 99%
“…Twelve tetrodes were implanted in the medial prefrontal cortex, and single units were recorded from the prelimbic and infralimbic cortex. Putative single units were isolated off-line by manual cluster cutting of various spike waveform parameters [19]. The experimental protocol was approved by the Institutional Animal Care and Use Committee of the Ajou University School of Medicine.…”
Section: Methodsmentioning
confidence: 99%